Síndrome de Woodhouse Sakati - Aranda, Franklin (2008)
We present a rare case of Woodhouse-Sakati syndrome in an 11 year-old patient, who presented congenital alopecia, bilateral sensorineural hearing loss, insulindependent diabetes mellitus, primary hypogonadism, psychomotor retardation, interventricular communication, decreased IGF1. The evolution and supportive treatment were satisfactory.